2021
DOI: 10.21608/ijma.2021.182971
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Donor Administration For improvement of Uterine Blood Flow in Unexplained Recurrent Pregnancy Loss

Abstract: Background: Recurrent pregnancy loss is still a challenging obstetric condition. It linked to impaired uterine blood, and vasodilators seem to prevent recurrent pregnancy loss. The aim of the work:The current study aimed to compare between investigate the Doppler uterine artery indices in females with recurrent pregnancy loss [unexplained]. It also aimed to study the effect of intravaginal isosorbide mononitrate, on the pattern of uterine blood flow. Materials and Methods: This observational, nested case contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Our results revealed that standard deviation ratio, pulsatility index (PI) and resistance index (RI) of the uterine-artery had fallen in IMN group with no significance difference in placebo group. In In agreement to our results El-Zahry, et al, 9 compared between the Uterine artery Doppler indices in women with unexplained recurrent miscarriages.…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed that standard deviation ratio, pulsatility index (PI) and resistance index (RI) of the uterine-artery had fallen in IMN group with no significance difference in placebo group. In In agreement to our results El-Zahry, et al, 9 compared between the Uterine artery Doppler indices in women with unexplained recurrent miscarriages.…”
Section: Discussionsupporting
confidence: 93%